2001
DOI: 10.1021/cr990134z
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Azetidin-3-ones, Oxetan-3-ones, and Thietan-3-ones

Abstract: I. Introduction 29 II. The Chemistry of Azetidin-3-ones 29 A. Structural Data 29 B. Synthetic Methods for Azetidin-3-ones 31 B.1. Carbonyl Group Generation in the Azetidine Ring 31 B.2. Intramolecular Cyclization Reactions 34 B.3. 1,3-Dipolar Cycloaddition Reactions 36 C. Chemical Properties of Azetidin-3-ones 37 C.1. Transformations of the Carbonyl Group 37 C.2. Condensation Reactions − Synthesis of 2-Benzylideneazetidin-3-ones 40 C.3. Ring Transformations of Azetidin-3-ones 40 C.4. Miscellaneous 41 III. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 210 publications
(735 reference statements)
0
62
0
Order By: Relevance
“…Since 1960, [ 3 ] it is known that primary amines react with epichlorohydrin to give the corresponding chlorohydrin, which subsequently can be transformed to the respective epoxide via addition of base. [ 4 , 5 ] On the other hand, this chlorohydrin can be spontaneously transformed into an azetidinium compound via internal cyclization.…”
Section: Methodsmentioning
confidence: 99%
“…Since 1960, [ 3 ] it is known that primary amines react with epichlorohydrin to give the corresponding chlorohydrin, which subsequently can be transformed to the respective epoxide via addition of base. [ 4 , 5 ] On the other hand, this chlorohydrin can be spontaneously transformed into an azetidinium compound via internal cyclization.…”
Section: Methodsmentioning
confidence: 99%
“…Chemerda et. al also reported that steroids involving oxetan-3-ones possessed novel bioactivity, such as antiinflammatory and antiglucocorticoid [5]. Owing to the considerable diversity of possible oxetanthe synthetic approaches to oxetan-3-ol was urgent to develop, and actually there are a limited number of routes described.…”
Section: Introductionmentioning
confidence: 99%
“…Our synthetic route was shown in scheme 1. Our route commenced with commercially available epoxy chloropropane (5). In the presence of catalytic anhydrous Iron (Ш) chloride (without further drying), epoxy chloropropane reacted with acetic acid at 70℃ to give (4) in 90% yield.…”
Section: Introductionmentioning
confidence: 99%
“…azetidin-2-ones) are a rich source of antibiotics, [2] their structural isomer (azetidin-3-ones) with the carbonyl group one carbon removed from the nitrogen atom, have not been found in nature but could serve as versatile substrates for the synthesis of functionalized azetidines. [3] The synthesis of azetidin-3-ones [3] has been mainly realized by acid-promoted or metal-catalyzed decomposition of a-amino-a'-diazo ketones [4] and 4-exo-tet cyclizations of aamino ketones. The diazo ketone approach is the most reliable in terms of substrate scopes, but it often suffers from competitive reactions and low yields; [4b, 5] moreover, diazo compounds are toxic and potentially explosive.…”
mentioning
confidence: 99%
“…Notably, 3 n was formed with 81 % ee from the corresponding sulfinamide (d.r. 91:9), [23] Moreover, the parent N-tert-butylsulfinylazetidin-3-one 3 o was readily prepared using [Et 3 PAuNTf 2 ] as the catalyst [Eq. (2)].…”
mentioning
confidence: 99%